Dukungan Keluarga dengan Tingkat Kesiapan Siswa dalam Menghadapi Ujian Kelulusan pada Siswa - Linda Ishariani; Laviana Nita Ludyanti (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
The Graduation Exam is now replaced with an assessment, the new policy causes many of them to feel anxious and unprepared physically, psychologically, and materially, hence the need for support from the closest people, namely the family in the form of instrumental, informational, emotional support and assessment/appreciation. This study aims to determine the relationship of family support to the level of readiness of students to take the graduation exam. This study uses a non-experimental design with a correlational research design through a cross sectional approach. The sample of this research is the 12th grade students of Fashion Design with a total of 35 respondents using the Total Sampling technique. Collecting respondent data using a questionnaire in the form of a google form link. Data were analyzed using Spearman Rank Test. The results showed that most of the family support was in the Enough category (65.7%), the level of readiness of almost all respondents (77.2%) was in the Enough category. The results of the Spearman Rank analysis are known to have p value = 0.000 with a = 0.05 and the value of the Correlation Coefficient (r) is 0.754. This study shows that family support with a child's readiness level is at a strong level in the same direction. This means that the higher the family support, the higher the readiness level of the child to take the national exam. Family support in the Enough category is one of the factors in changing the level of readiness of children to take the graduation exam. The optimal support in this study is informational support, which is 76.58% and is included in the good category. So it is recommended for families to provide other family support, namely emotional, instrumental, and even more optimal support so that students feel themselves cared for and make children excited to learn and prepare to take the graduation exam in the upcoming Covid-19 pandemic.